Structural Performance of Blind Bolt Shear Connector under Static Loading. Issue 2 (1st September 2021) - Mirza, Olivia; Hosseini, Seyedeh Maryam; Mamun, Mohammad Shafiqul; kuikel, kiran; Mashiri, Fidelis
Abstract: The main goal of this research paper is to determine the shear strength of blind bolt shear connectors for composite structures under static loading. The blind bolt shear connectors are not commonly used in composite structures due to the lack of detailed research regarding the structural performance of these types of connections. Whereas, the use of blind bolt shear connectors in strengthening and retrofitting of existing composite structures can be potentially sustainable and a cost‐effective approach. Hence, in this paper, the mechanical behaviour of blind bolt shear connectors was experimentally examined using direct shear tests. In addition, a three‐dimensional finite element model was developed to evaluate the factors that influence the static strength of steel‐concrete composite beam with bolted shear connectors. Furthermore, the numerical and experimental results were plotted and compared with conventional headed stud shear connector in terms of load versus slip. Results showed that the blind bolt shear connectors had significantly higher static strength than headed stud.